Energy, macronutrients, and sensory characteristics of gluten-and casein-free (GFCF) mocaf biscuits substituted with kidney bean and keluih seed flour for children with autism - Niza Iana Tzani; Nurmasari Widyastuti; Hartanti Sandi Wijayanti; Fillah Fithra Dieny; Lisa Rosyida Nurhidayati (AcTion: Aceh Nutrition Journal, 2025)
Autism is often associated with macronutrient deficiencies due to food sensory preferences, as well as gluten and casein allergies, which can trigger digestive disorders. In this study, gluten- and casein-free (GFCF) biscuits were developed by substituting kidney bean flour and keluih seed flour, followed by an evaluation of their energy content, macronutrient composition, and sensory characteristics to determine the best formulation. Four formulas were tested: F0 (100:0:0), F1 (30:52.5:17.5), F2 (30:35:35), and F3 (30:17.5:52.5). Macronutrient content was analyzed using standard laboratory methods (Kjeldahl, Soxhlet, and difference), whereas energy was calculated based on macronutrients. The hedonic test involved 50 untrained panelists, and statistical analysis was conducted using One-Way ANOVA, Kruskal-Wallis test, and a multi-attribute decision compensatory model. The biscuits contained 432–455 kcal of energy, 3-8% protein, 30-32% fat, and 32-40% carbohydrate. Significant differences were observed in energy (P =0,028), protein (P <0,001), fat (P =0,005), and carbohydrate (P <0,001), as well as sensory preferences for taste (P <0,001), aroma (P =0,002), and overall preference (P =0,017). F1 was selected as the best formulation because of its favorable sensory score and balanced nutrient content. Kidney bean flour improved protein and sensory properties, while keluih seed flour increased energy and fat but lowered preference levels. This product offers practical potential as a GFCF snack to support the dietary management of children with autism.